Correction: A tetramer micelle: the smallest aggregation number corresponding to the vertex number of regular polyhedra in platonic micelles. Issue 6 (26th January 2018) - Fujii, Shota; Takahashi, Rintaro; Lee, Ji Ha; Sakurai, Kazuo
Abstract : Correction for 'A tetramer micelle: the smallest aggregation number corresponding to the vertex number of regular polyhedra in platonic micelles' by Shota Fujii et al., Soft Matter, 2018, DOI: ; Web:10.1039/c7sm02028g .